Z problematyki przestrzeni w komedii plebejskiej XVI i XVII w. - Pirecki, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
This text says about space in people’s comedies of 16th and 17th centuries and the elements, that create it. There is one conclusion of this article – in one particular comedy we may find many forms of space, both theatrical space and the dramatic one.